HYDROLOGICAL DISASTERS AND HUMAN HEALTH: SCOPING REVIEW - de Sousa, Gregório Neto Batista; de Carvalho, Emerson Machado; Borges, Grasiely Faccin; de Jesus Junior, Renan Borges; Donatti, Adriano Frederico (Seven Editora, 2026)
The objective of this scoping review is to evaluate literature between 2013 and 2023 focused on human health and hydrological disasters. The research databases were: Lilacs, Medline via PubMed, Scopus, Web of Science, ScienceDirect. Eligibility was determined using inclusion and exclusion criteria, and the search strategy included: (Health) AND (Hydrologic Disaster), (Health Risk) AND (Hydrologic Disaster). Initially, 58 articles were selected, but after systematic screening, only 12 were relevant to the topic. The results indicated that the prevalence of post-disaster infectious diseases is a recurring and relevant theme in the literature. In short, scientific collaboration highlighted the need for more comprehensive and multidisciplinary work, with the potential to act in the formulation of public policies and international partnerships, preparation of health managers and professionals, development of plans, research and interventions in the relationship between health and hydrological disasters.